Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1002/hep.26525
|View full text |Cite
|
Sign up to set email alerts
|

CD73 (ecto-5′-nucleotidase) hepatocyte levels differ across mouse strains and contribute to mallory-denk body formation

Abstract: The formation of hepatocyte Mallory-Denk bodies (MDBs), which are aggregates of keratins 8 and 18 (K8/K18), ubiquitin, and the ubiquitin-binding protein p62, has a genetic predisposition component in humans and mice. We tested the hypothesis that metabolomic profiling of the MDB-susceptible C57BL and the MDB-resistant C3H mouse strains can illuminate MDB-associated pathways. Using both targeted and unbiased metabolomic analyses we demonstrated significant differences in intermediates of purine metabolism. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
41
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 31 publications
3
41
0
Order By: Relevance
“…Lastly, our data showing down-regulation of mouse Nt5e gene expression in fibrotic liver and activated myofibroblasts are in agreement with previous reports describing an overall decrease in Nt5e gene expression is observed in experimental mouse models of chronic liver injury such as chronically feeding with cholestasis inducer 3,5-diethoxycarbonyl-1,4-dihydrocollidine compound or long-term exposure to oxidative stress inducer cerium trichloride [48,49]. Additionally, human liver NT5E mRNA expression is decreased in biopsies from patients with established fibrosis secondary to hepatitis C infection or non-alcoholic fatty liver disease [48].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Lastly, our data showing down-regulation of mouse Nt5e gene expression in fibrotic liver and activated myofibroblasts are in agreement with previous reports describing an overall decrease in Nt5e gene expression is observed in experimental mouse models of chronic liver injury such as chronically feeding with cholestasis inducer 3,5-diethoxycarbonyl-1,4-dihydrocollidine compound or long-term exposure to oxidative stress inducer cerium trichloride [48,49]. Additionally, human liver NT5E mRNA expression is decreased in biopsies from patients with established fibrosis secondary to hepatitis C infection or non-alcoholic fatty liver disease [48].…”
Section: Discussionsupporting
confidence: 81%
“…Additionally, human liver NT5E mRNA expression is decreased in biopsies from patients with established fibrosis secondary to hepatitis C infection or non-alcoholic fatty liver disease [48]. In contrast, upregulation of mouse Nt5e gene expression has been reported in experimental models acute liver injury such as ethanol-induced steatosis and thioacetamide-induced acute liver failure [50,51].…”
Section: Discussionmentioning
confidence: 89%
“…We found that MCD diet induced an increase in K8 mRNA, and DDC treatment blocked the increase. It has been demonstrated that CD73 contributes to experimental MDB induction and is highly regulated in MDB‐associated liver injury in mice (Snider et al ., ). In this study, mice on MCD diet for 8 weeks induced the expression of CD73, while DDC treatment inhibited the expression of CD73.…”
Section: Discussionmentioning
confidence: 97%
“…As a potential mechanism driving the conformational change of K8, murine MDB formation is associated with impaired chaperone function and decreased levels of Hsp72, the prototypical stress‐inducible heat shock protein . Studies in different mouse strains also manifested a significant genetic predisposition to MDB formation and several modifier genes have been identified …”
mentioning
confidence: 99%
“…MDBs represent a characteristic feature distinguishing simple steatosis from NASH; however, this feature is present only in a subset of patients . Given the known genetic component in both NASH development and MDB formation, we tested the hypothesis that a diet rich in saturated fatty acid, i.e., an established murine model of diet‐induced obesity and a major alimentary factor responsible for NASH development, triggers MDB appearance and liver injury in susceptible individuals. Indeed, a high‐fat (HF) diet promoted/induced MDB formation and development of hepatic injury/inflammation in both the DDC‐fed animals as well as the K8 overexpressing mice .…”
mentioning
confidence: 99%